Pengembangan Media Pembelajaran Buku Digital Interaktif Berbasis Pendekatan Matematika Realistik untuk Meningkatkan Kemampuan Spasial Siswa - Cici Puspaningrum; Edi Syahputra; Edy Surya (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to: 1) develop an interactive digital book learning media based on a realistic mathematics learning approach on the valid, practical, and effective flat-sided geometry material (cubes and blocks) so as to improve students' mathematical spatial abilities; 2) improve students' mathematical spatial abilities by using interactive digital books based on a realistic mathematics learning approach on the flat side (cube and block) material. This research is a development research using the ADDIE model. The validity of the interactive digital book learning media assessed by the validators in terms of three aspects, namely the quality of content and objectives, learning/instructional strategies, and media design obtained a total average of 3.73 ("valid" category). The practicality of learning media is seen from the observation score of learning implementation in the first trial, which is 2.87 (category "poorly implemented") so that the second trial is carried out and a score of 3.73 is obtained (category "well implemented"). The effectiveness of learning media in terms of four aspects, namely classical completeness, student activity observation scores, observations of teachers' ability to manage learning, and student responses. The classical mastery of the students' mathematical spatial ability in the second trial was 86.67% (13 students). The average percentage of achievement of the ideal time of student activity in the second trial for three meetings was 22.2%, 26.87%, 26.87%, 13.9%, 7.87%, and 2.32%. The average score for observing the teacher's ability to manage learning in the second trial was 3.79 ("good" category). The average student response in the second trial was 3.74 ("interested" category). Based on the normalized gain index, it was found that in the second trial there was an increase in the value with a score of 0.40 ("medium" criteria).Keywords: Interactive Digital Books, Realistic Mathematics Learning Approach, Spatial Ability, Development of Mathematics Learning Media, Cubes and Blocks.